The Strategic Role of BMT as a Non-Bank Islamic Financial Institution in Empowering MSMEs in Indonesia - Nasywa Salsabila Wahdoni; Nida Ummu Rofikoh (Takaza Innovatix Labs Ltd., 2025)
Structural poverty in Indonesia reached 8.57% in September 2024, making MSMEs a primary strategy for alleviation despite being hampered by limited capital and managerial skills. This study aims to describe and analyze the strategic role of Baitul Maal wat Tamwil (BMT) as a non-bank Islamic financial institution in empowering MSMEs through Islamic financing and mentoring. A qualitative library research method was used, with a literature population of 2019-2025 from Sinta/Scopus/Google Scholar, a purposive sample of 50+ relevant documents. Secondary data instruments were analyzed through reduction, thematic presentation, triangulation, and content analysis. The results show that BMT provides murabahah, mudharabah, musyarakah, ijarah, qardh al-hasan financing, plus training that increases MSME productivity, supported by QS. Al-Baqarah: 188 and cooperative regulations. The conclusion states that BMT creates sustainable financial inclusion; socialization, innovation, and collaboration are recommended to overcome literacy and capital constraints